The role of Green Public Procurements in energy transition: The case of Western Macedonia - Pavlos Kilintzis; Elpida T. Samara; Lefteris Topaloglou; Giorgos Avlogiaris; Dimitrios Kafetzopoulos (Journal of Innovation and Entrepreneurship, 2023)
This paper aims to assess the level of implementation of Green Public Procurements (GPP) in the Region of Western Macedonia-Greece, which is currently under energy transition from lignite to a RES-based energy model. By that assessment, a linkage between the GPP framework and energy transition is created, revealing the distinct GPP criteria that should be adopted by energy-transition regions, which have the potential to strengthen the transition process. Rather than implementing the total number of the GPP criteria, literature and methodology findings indicated that specific GPP criteria are directly connected to energy transition and should be primarily adopted by policymakers in comparison to the rest. These criteria are Electricity, Road Transport, Waste Water Infrastructure and Road Lighting and Traffic Signals. By assessing a sample of 31 procurement officials and scientific experts in the five major municipalities of the region, the implementation level of GPP criteria was measured average-to-low, implying that there is a considerable scope by the region's main municipal authorities to adopt them to a greater extent. Statistical correlations using Spearman's rank correlation analysis between specific GPP criteria were also identified, indicating distinct interconnections between the criteria pairs that imply commonalities in the implementation framework of GPP. The paper's implications for future research led to the identification of specific GPP criteria in the public procurement process, that have the potential to enhance green sustainability and boost energy transition.
Keywords: 650; GPP criteria; Green energy transition; Green Public Procurement